Congenital Anomalies: An Analysis of a Myth on Sumerian Clay Tablets - Agartan, Canan Aldirmaz; Oner, Sema (ORTADOGU AD PRES & PUBL CO, 2010)
Objective: In this study, the 4(th), 5(th), 6(th) and 7(th) babies born with different anomalies that had been described in the Sumerian myth of Enki and Nimnah: Creation of Man, have been evaluated. Material and Methods: The myth was evaluated with the help of archeological sources, online museum catalogues, reviews written on this subject and getting opinions of various experts. Results: In the first part of the myth, a feast given by the gods to celebrate the creation of the perfect man had been described. In the second part, the Goddess Nimnah, had become jealous of Enki's success and created 6 defective, crippled babies out of mud. As Enki had got angry with Nimnah's act, he had created the 7(th) defective baby. Based on the descriptions of the babies in the myth, the 4(th) one had urinary continence, the 5(th) one was an infertile girl, the 6(th) one had ambigious genitalia, and the 7(th) one had probably Wolf-Hirschhorn syndrome. The creations of these seven babies were done during above-mentioned feast under the influence of alcohol. To the best of our knowledge, this myth presented on the Sumerian clay tablets has an importance as they are the first written documents describing urinary incontinence, infertility and ambigiuous genitalia. Conclusion: It can be speculated that, Sumerians, who had pioneered various fields of science and technology might have observed the teratogenic effects of parental use of alcohol and wanted to send a message to the following generations by this myth.
Keywords: Congenital abnormalities; fetal alcohol syndrome; civilization; General & Internal Medicine